ANALISIS PERAN PENDIDIK PKN DALAM MEMOTIVASI BELAJAR PESERTA DIDIK - Emilia Emilia; Bambang Budi Utomo; Ika Rahmatika Chalimi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to determine the Role of Citizenship Education Teachers in Motivating Student Learning in Class VII A SMP Negeri 3 Ketungau Tengah, Sintang District. The research method used is descriptive with a qualitative research form. The data source of this research was students of class VII A and the data were obtained from the administration of SMP Negeri 3 Ketungau Tengah, Sintang District. The results of the study 1) The conditions of learning were less conducive, because students seemed not to participate in learning activities well. 2) The way Civics teachers motivate student learning is to provide questions and feedback, and always help students when learning difficulties. 3) The obstacles faced by the teacher are the lack of student interest in Civics lessons, the influence of peers, the lack of attention and supervision from parents and the lack of Civics class hours. 4) The efforts of the teacher in overcoming obstacles, namely fostering student interest in Civics lessons, giving advice and giving appeals to parents of students as well as adding Civics activities.Keywords : The Role of the Teacher, Motivating Student Learning.